The Great Bend People - A Prelude to History - Wade Parsons (Symphony in the Flint Hills, 2009)
When conquistadors Coronado (1541) and Onate (1601) journeyed into Kansas, the possibilities of unimaginable wealth, lost souls, and eternal glory drove their expeditions across an uncharted wilderness. Their destination was the gold-filled land of Quivira. In Kansas these Spaniards found no gold, established no missions, and were ultimately disgraced by their king. What they encountered were etensive settlements of semi-sedentary agriculturists who effectively utilized their local resources. These people are known today as the Wichita tribe and are referred to as the Great Bend Aspect (ca AD 1450-1700) by archeologists.
Keywords: Native Americans; Indians; Flint Hills; Kansas; expeditions; Spain; exploration; contact; tools; weapons; creating; crafting; natural; construction; housing; houses; craftsmanship; ancient; arrowhead; fight; crops; farmer; farming